The Impact of E-government and E- business on Economic Performance: A Comparative Study of Developing and Developed Countries - Srivastava, Shashi Kant; Kumar Panigrahi, Prabin (The journal of contemporary issues in business and government, 2016)
In the last decade, there has been a significant growth in applications of e-business as well as e-government in many countries. Research shows that e-business and e-government contribute to the economic performance of countries. The objective of this study is to explore the relationship between e-government as well as e-business and economic performance of developing and developed nations, separately. This paper argues and finds that the relationship between e-government as well as e-business and economic performance varies based on the development status of a country given the differences in the technological, organisational and environmental factors between developed and developing nations. More specifically, the results show that e-government is significantly related to economic performance in the case of developing countries and e-business is significantly related to economic performance in developed countries.